A Survey of Dog Owners' Attitudes toward Treats. Issue 1 (2nd January 2020) - Morelli, G.; Marchesini, G.; Contiero, B.; Fusi, E.; Diez, M.; Ricci, R.
ABSTRACT: Commercially available dog treats have become very popular and a common part of the pet's diet, yet very little is known about peoples' opinions and feeding habits; therefore, a survey was shared on a popular social network. Most of the self-selected interviewed owners (n = 1833, 83%) use treats regularly, mainly to reward their dog's behavior or during training-sports activities. Owners usually buy several types of treats, of which biscuits and dental care sticks are the most common, and usually hand out one to five pieces to their dogs every day. Most owners read the labels of the treats to seek the ingredients list and the claimed health benefits; contrarily, many owners look for non-nutritional values, such as flavor (n = 321, 18%), brand (n = 72, 4%) or shape (n = 46, 3%). Seventy-five percent of the owners (n = 1369) follow the feeding instructions provided by the producers on the label. Treat feeding is a common practice among dog owners and there is great variability among regimens (e.g., types and quantities provided). Understanding the owner's attitudes could help veterinarians educate them to manage treats in the dog's diet.